In search of heart barometer—advantage of left atrial dimension over electrocardiographic indices of left ventricular hypertrophy in arterial hypertension - Bogusława Nowak; Rafał Nowakowski; Aleksandra Gapys; Tomasz Rechciński; Ewa Trzos; Małgorzata Kurpesa; Piotr Lipiec; Jarosław D. Kasprzak; Karina Wierzbowska-Drabik (Exploration of Cardiology)
Aim: Left ventricular (LV) hypertrophy (LVH) is a common and relevant complication of arterial hypertension (AH) and 12-lead electrocardiogram (ECG) is widely used for its preliminary assessment. The aim of the study was to compare the correlations of four ECG-derived criteria of LVH and left atrial (LA) anteroposterior diameter with LVH assessed by echocardiography and expressed as left ventricular mass (LVM) index (LVMI) in search of the most accurate preliminary indicator of LVH. Methods: The study included 61 subjects with AH [age (year) 69 ± 10, 17 females] and 27 without AH, (age 40 ± 9, 10 females) evaluated with 12-lead ECG and transthoracic echocardiography (TTE). As the ECG-based criteria of LVH Sokolow-Lyon index (SLI), Cornell voltage (CV), Cornell product (CP), and Romhilt-Estes point score (RES) system were evaluated. The ECG indices and LA diameter were correlated with LVMI and correlations coefficients were compared. Results: Among ECG-LVH indicators SLI showed the closest correlation with LVMI [rank correlation coefficients (rho) = 0.38, P < 0.0001], followed by CV and CP with rho = 0.33, P = 0.002 and rho = 0.32, P = 0.002, respectively, whereas RES did not correlate significantly with LVMI. The strongest correlation with LVMI was found for the LA diameter with rho = 0.73 and P < 0.0001, showing an even stronger correlation in women—rho = 0.8 (P < 0.0001) vs. rho = 0.65 (P < 0.0001) in men. In the multivariate analysis, the LA was the only independent predictor of the increased LVMI with R2 = 0.52, P < 0.0001. Conclusions: LA diameter outperformed significantly the ECG indices as far as the correlation with LVMI was concerned and emerged as the only independent predictor of mild and moderate LVH in hypertensive patients. Among the ECG criteria, the strongest correlation was shown for SLI, followed by CV and CP indices.